Contextualizing the organizational mindset - CARPINI, Joseph A. (Institutional Knowledge at Singapore Management University, 2022)
Although Schneider and Pulakos (2022, p. 2) call for scholars to adopt an “organizational mindset,” which includes “an increased organizational frame of reference on variables of interest,” the authors have overlooked the importance of contextualizing such a mindset. Contextualizing “entails linking observations to a set of relevant facts, events, or points of view that make possible research and theory that form part of a larger whole” (Rousseau & Fried, 2001, p. 1). Contextualizing is essential because it provides a common vernacular that facilitates the valid and reliable extension of the industrial-organizational (I-O) mindset to the study of organizational differences and effectiveness. According to Rousseau and Fried, there are six features scholars and practitioners should consider when contextualizing research. These features are levels, time, representativeness, point of view, range restriction, and construct comparability. By systematically considering the features of contextualizing, scholars can distinguish organizations based on salient characteristics that can influence the behavior of people and shape the relationship among variables (Johns, 2006).